Polarization of ILC2s in Peripheral Blood Might Contribute to Immunosuppressive Microenvironment in Patients with Gastric Cancer - Qingli Bie; Pan Zhang; Zhaoliang Su; Dong Zheng; Xinyu Ying; Yumin Wu; Huijian Yang; Deyu Chen; Shengjun Wang; Huaxi Xu (Journal of Immunology Research)
Newly identified nuocytes or group 2 innate lymphoid cells (ILC2s) play an important role in Th2 cell mediated immunity such as protective immune responses to helminth parasites, allergic asthma, and chronic rhinosinusitis. However, the contributions of ILC2s in the occurrence and development of cancer remain unknown. Our previous study found that there was a predominant Th2 phenotype in patients with gastric cancer. In this study, the ILC2s related genes or molecules in PBMC from patients with gastric cancer were measured, and the potential correlation between them was analyzed. The expression levels of RORα, GATA3, T1/ST2, IL-17RB, CRTH2, IL-33, IL-5, and IL-4 mRNA were significantly increased in patients, but no significant changes were found in ICOS, CD45, and IL-13 expression, and there was a positive correlation between RORα or IL-13 and other related factors, such as ICOS and CD45. The increased frequency of ILC2s was also found in PBMC of patients by flow cytometry. In addition, the mRNA of Arg1 and iNOS were also significantly increased in patients. These results suggested that there are polarized ILC2s in gastric cancer patients which might contribute to immunosuppressive microenvironment and closely related to the upregulation of MDSCs and M2 macrophages.